2021
DOI: 10.7759/cureus.16022
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Predictors of Major Bleeding After Transcatheter Aortic Valve Transplantation Using the National Inpatient Sample (2015–2018)

Abstract: BackgroundTranscatheter aortic valve replacement (TAVR) is now a common procedure to treat and improve quality of life, clinical outcomes, and self-sufficiency in high-risk patients with aortic stenosis, and its use has been expanding rapidly in younger and low-risk populations. The aim of this study was to evaluate the outcomes, trends, and predictors of major bleeding in patients undergoing TAVR. MethodologyWe utilized the National Inpatient Sample (NIS) data from the year 2015 to 2018. International Classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In the present study, approximately 7% of patients who underwent TAVR had BARC 3 or 5 type bleeding at one year, which is consistent with recent reports [5,7]. A previous study reported that life-threatening bleeding after TAVR, as defined by the VARC criteria, occurred in approximately 15 to 20% of TAVR procedures [22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, approximately 7% of patients who underwent TAVR had BARC 3 or 5 type bleeding at one year, which is consistent with recent reports [5,7]. A previous study reported that life-threatening bleeding after TAVR, as defined by the VARC criteria, occurred in approximately 15 to 20% of TAVR procedures [22].…”
Section: Discussionsupporting
confidence: 92%
“…Major bleeding or vascular complications have decreased as TAVR technology evolves into smaller device and sheath sizes [22,23] and bleeding complications are inconsistent in the early literature [24]. However, major bleeding is still associated with a three-fold increase in one-year mortality following TAVR [5][6][7]. Patients referred to TAVR are elderly, frail and at risk for both bleeding and ischemic complications [7,17,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent National Inpatient Sample analysis of patients undergoing TAVR found that end-stage renal disease and coagulopathy were the most significant predictors of major bleeding. 21 A large, German singlecentre analysis of patients undergoing TAVR with third-generation devices, as well as the Perclose ProGlide ® system (Abbott Vascular, Chicago, IL, USA), found that higher sheath-to-femoral-artery ratio and more than two vessel entries with large-bore sheaths were significant predictors of access-related vascular complications (p<0.001 and p=0.029, respectively). 22 Recently, a TAVR-specific bleeding risk model was developed and validated with the patient populations of two large European registries; in this study, machine learning selected six variables to generate a bleeding risk score: blood haemoglobin, serum iron, creatinine clearance, common femoral artery (CFA) diameter, oral anticoagulation and dual antiplatelet therapy.…”
Section: Bleeding Risk Factors For Transcatheter Aortic Valve Replace...mentioning
confidence: 99%